A broad antibody with enhanced HIV-1 neutralization via bispecific antibody-mediated prepositioning - Soohyun Kim; Caelan E. Radford; Duo Xu; Jianing Zhong; Jonathan Do; Dominic M. Pham; Katie A. Travisano; Maria V. Filsinger Interrante; Theodora U. J. Bruun; Valerie Rezek; Bailey Wilder; Martina Palomares; et al. (Nature Communications)
Abstract Antibodies targeting the highly conserved prehairpin intermediate (PHI) of class I viral membrane-fusion proteins are generally weakly neutralizing and are not considered viable therapeutic agents. We previously demonstrated that antibodies targeting the gp41 N-heptad repeat (NHR), which is transiently exposed in the HIV-1 PHI, exhibit enhanced broad neutralization in cells expressing the Fc receptor, FcγRI. To enhance neutralization in cells lacking FcγRI, we here develop a bispecific antibody (bsAb) by fusing an NHR-targeting antibody to an antibody against CD4, the HIV-1 receptor on T cells. The bsAb provides a 5000-fold neutralization enhancement and shows unprecedented neutralization breadth compared to existing broadly neutralizing antibodies. Importantly, the bsAb reduces viral load in HIV-1-infected humanized male mice, and viral envelope sequencing under bsAb pressure revealed an NHR mutation that potentially impairs viral fitness. These findings validate the NHR as a potential HIV-1 therapeutic target, setting the stage for a new class of broadly neutralizing antibodies.